MATHEMATICAL CRITICAL THINKING SKILLS PROFILE REVIEWED FROM ACADEMIC PROCASTINATION - Gunawan, Gunawan; Saudah, Saudah; Setyaningsih, Eka; Kusuma, Jaka Wijaya (International Journal of Multidisciplinary Research and Literature, 2025)
This research aims to describe students' mathematical critical thinking abilities in terms of the level of academic procrastination. The research method used is descriptive qualitative with data collection techniques through questionnaires, observation, interviews and documentation. The subjects of this research were students in class VIII A of SMP Muhammadiyah Larangan on straight line equations. Data analysis was carried out using triangulation, namely comparing data from various sources (questionnaires, interviews and observations) to obtain a more comprehensive understanding.The research results show that: 1) Students with high academic procrastination are unable to carry out interpretation, analysis, problem solving, evaluation, or inference; 2) Students with moderate academic procrastination are able to carry out interpretation and analysis, but are unable to carry out problem solving, evaluation and inference; 3) Students with low academic procrastination are able to carry out interpretation, analysis, problem solving, evaluation and inference well. The results of this study indicate that students' level of academic procrastination has a significant impact on their mathematical critical thinking abilities. Students with high procrastination tend to experience difficulties in interpreting, analyzing and solving problems, which indicates the need for more effective intervention in the learning process. Developing learning strategies that can reduce procrastination, such as implementing time management techniques, increasing motivation, and implementing active learning methods, is very important. Schools and educators can create an environment that supports the development of students' critical thinking skills, which in turn will improve their overall academic performance